2019
DOI: 10.3233/jad-180943
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Brain Atrophy and Cognitive Decline Comparing a Sample of Community-Dwelling People Taking Angiotensin Converting Enzyme Inhibitors and Angiotensin Receptor Blockers Over Time

Abstract: These results support the theory that ARB may be preferable to ACEi to reduce brain atrophy. The mechanisms underlying this differential association warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…152 A recent longitudinal analysis following non-demented subjects 55 to 90 years of age found that participants utilizing an ARB had slower brain atrophy rates compared to those taking ACEIs. 153 It was also demonstrated that AD patients utilizing ARBs exhibited a 9.4% slower decline in delayed recall performance compared to those who utilized ACEIs. ARB use was also associated with better performance over time on the Trail Making Test (TMT-A) and the Digit Symbol Substitution Test (DSST), both of which assess attention and psychomotor processing speed.…”
Section: 83mentioning
confidence: 98%
“…152 A recent longitudinal analysis following non-demented subjects 55 to 90 years of age found that participants utilizing an ARB had slower brain atrophy rates compared to those taking ACEIs. 153 It was also demonstrated that AD patients utilizing ARBs exhibited a 9.4% slower decline in delayed recall performance compared to those who utilized ACEIs. ARB use was also associated with better performance over time on the Trail Making Test (TMT-A) and the Digit Symbol Substitution Test (DSST), both of which assess attention and psychomotor processing speed.…”
Section: 83mentioning
confidence: 98%
“…Through successive analyses for different AHMs groups, the current study demonstrated that in patients with hypertension and MCI, ARBs were associated with a lower risk of progression to dementia compared with ACE inhibitors and other classes of AHMs, which was consistent with several studies in that ARBs provided more neuroprotection than ACE inhibitors. 13,14,[16][17][18]26 In an older study in the ADNI, 15 Hajjar et al found that ARBs were associated with a longitudinal decrease in CSF tau in patients with MCI. However, evidence based on biomarkers alone is insufficient, and there is a gap between these biomarkers and the clinical dementia outcome, especially when the underlying mechanisms are still not fully understood.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The little data available suggest that cognitively intact individuals on ARB have slower atrophy rates and less cerebral amyloid-beta deposition than those on ACEI. 46,47 The "angiotensin hypothesis" ideally requires RCT testing. Trials comparing antihypertensive subclasses with dementia as primary outcome are however challenging,…”
Section: A C C E P T E Dmentioning
confidence: 99%